Analisis Pengetahuan Tugas Perkembangan Keluarga Dengan Perilaku Orang Tua Dalam Penggunaan Gawai Pada Anak Usia Pra Sekolah - Tressia, Tressia Febrianti; Masdiana; Desi Afriyanti; Gian Hawara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
Technological advances can be utilized by all groups, including preschool children (3-6 years), information technology that is very familiar to children is gadgets. Parental behavior will be a real example of gadget use in children, in addition, the use of gadgets in children can affect family processes and family development. The purpose of this study is to analyze knowledge of family development tasks with parental behavior in the use of gadgets in children. This study uses a cross-sectional study design on 106 preschool children in Kampung Rumbut, Cimanggis District, Depok City. The results of statistical tests using the chi square test (α = 0.05) obtained a relationship between knowledge of family development tasks and parental behavior in the use of gadgets in preschool children, the results showed parental behavior on parental attitudes in the use of gadgets in children p = 0.000 (<α 0.05), parental self-control behavior p = 0.000 (<α 0.05), on the behavior of parents and children in the use of gadgets p = 0.025 (<α 0.05). Parents must be able to understand the proper and appropriate use of gadgets for their children. Parents must be able to control themselves in gadget use,